2014
DOI: 10.7566/jpsj.83.064703
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Polarized Majorana Bound States inside a Vortex Core in Topological Superconductors

Abstract: We reveal that Majorana bound states inside the vortex core in an odd-parity topological superconductivity classified as "pseudo-scalar" type in the gap function are distinctly spin-polarized by solving the massive Dirac Bogoliubov-de Gennes (BdG) equation considering the spin-orbit coupling. This result is universal for "Dirac superconductivity" whose rotational degree of freedom is characterized by the total angular momentum J = S + L and in marked contrast to the spin-degeneracy of the core bound states as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…U sing this condition, we relate the pair am plitudes of odd- On the other hand, the expectation value of the spin at zero energy, i.e., the spin of MF [79][80][81] is given by Therefore we find that odd-frequency pair amplitudes and the ratio of (sz) and (sx) satisfy the following relation: r s odd _ r s odd r s odd Jn (17) In later sections, using Eq. (8), we discuss how odd-frequency pair relates with the parity of the wave function by our numerical results.…”
Section: Ic D J Imentioning
confidence: 99%
“…U sing this condition, we relate the pair am plitudes of odd- On the other hand, the expectation value of the spin at zero energy, i.e., the spin of MF [79][80][81] is given by Therefore we find that odd-frequency pair amplitudes and the ratio of (sz) and (sx) satisfy the following relation: r s odd _ r s odd r s odd Jn (17) In later sections, using Eq. (8), we discuss how odd-frequency pair relates with the parity of the wave function by our numerical results.…”
Section: Ic D J Imentioning
confidence: 99%
“…The superconducting topological insulator (STI), which is a superconductor realized in a doped topological insulator, has been also attracting a great research interest following the first observation of zero-bias conductance peak that indicates the existence of SABSs in Cu x Bi 2 Se 3 [26]. And now, determination of the pairing symmetry of Cu x Bi 2 Se 3 is recognized as an important problem [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. In the STI, theoretical studies have revealed that the cone shape SABS becomes twisted dispersion due to the mixing with the surface state in the normal state [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…2(c) shows that the Majorana state is spin-polarized in the helical p-wave SCs. This is another type of spin-polarized zero energy state than that supposed in Bi 2 Te 3 /NbSe 2 [18] or Cu x Bi 2 Si 3 [20].…”
Section: H Dependence Of Zero-energy Spin-polarized Dos and Ldosmentioning
confidence: 70%
“…Moreover, spin polarization of Majorana zero-energy modes are investigated by the spin-polarized STM/STS measurement, which can selectively detect the spin-dependent conductance [19]. The spin polarization in the vortex state of topological SC Cu x Bi 2 Si 3 is also theoretically studied [20].…”
Section: Introductionmentioning
confidence: 99%